Interactive global histories : for a new information environment to increase the understanding of historical processes - Nanetti, Andrea (2021)
The paper presents the results of an experimental case study on intercontinental trade, diplomacy, conflicts and other interactions among cities, nations and continents during Late Middle Age and Early Renaissance (1205-1533 CE). This study is based on Andrea Nanetti's ongoing research project Engineering Historical Memory (EHM) and conducted at Nanyang Technological University by Andrea Nanetti, Siew Ann Cheong, and Mikhail Filippov. The two main aims are to test: 1) ontologies to organize texts, images, and sounds in a relational database suitable to develop a systemic approach to the study of complex interactions among key subjects of the historical landscape, and 2) coherent narratives from growing historical data and metadata that can be tested at the same level of rigor as scientific hypotheses and theories. The vision is that the generation of such narratives, supported by a new coherent ontology, automatically and in a scalable way, can revolutionize the practice of historical studies.